Influence of geochemical reactions on the creep behavior of Mt. Simon sandstone. (December 2020) - Akono, Ange-Therese; Dávila, Gabriela; Druhan, Jennifer; Shi, Zhuofan; Jessen, Kristian; Tsotsis, Theodore
Highlights: The main fluid-rock reactions for Mt. Simon rock are feldspar and quartz dissolution. Incubation in CO2 -saturated brine leads to an increase in nano- and microporosity. Due to CO2 -induced reactions, the macroscopic creep modulus decreases. Computer vision provides a means to monitor CO2 -related mineralogical changes. Grid nano-indentation yields a deeper understanding of CO2 -induced geochemical reactions. Abstract: The capture and subsurface storage of carbon dioxide is a sustainable option that is currently pursued worldwide to mitigate greenhouse gas effect. However, predicting the long-term mechanical integrity of CO2 underground storage systems remains a challenge. To address that question, it is essential to understand the influence of fluid-rock chemo-mechanical interactions on the long-term and on the time-dependent mechanical properties. In turn, the long-term mechanical response and the time-dependent mechanical behavior can be represented by the creep response. We investigate the impact of CO2 -induced geochemical reactions on the creep response of Mt. Simon sandstone with a 50–400  μ m grain size. We perform static and dynamic flow experiments on Mt. Simon sandstone specimens under geological conditions, at a temperature of T = 50 –53  ° C and for CO2 pressures of P = 8.62, 17.2 MPa under both static flow and dynamic flow-through conditions. After aging, we employ creep indentation testing, high-resolution SEM-EDS, computer vision, machine learning, and micromechanics modeling to probe changes on the microstructure and mechanical properties. Following both static and dynamic flow-through experiments, we observe a 10–22% decrease in quartz volume fraction and an increase in both the microporosity (7–28%) and nanoporosity (60–65%). Additional CO2 -induced microstructural changes include an enlargement of pore throats and the formation of channels. These observations point to the presence of CO2 -induced K-feldspar dissolution and clay dissolution reactions. The macroscopic creep behavior is logarithmic and the macroscopic creep modulus varies depending on the microporosity and the relative quartz and feldspar content. As a result of these geochemical reactions and of the related microstructural changes, a 55–60% decrease in the macroscopic logarithmic creep modulus is predicted.